Smartphone-Based Peptide Nucleic Acid (PNA) Probe-Assisted Potentiometric Biosensor for Point-of-Care Testing of SARS-CoV-2 Nucleic Acid - Ozer, Tugba; Jampasa, Sakda; Lomae, Atchara; Ruecha, Nipapan; Sagdic, Osman; Vilaivan, Tirayut; Henry, Charles S.; Chailapakul, Orawon (AMER CHEMICAL SOC, 2026)
Herein, we present a potentiometric biosensor based on amine magnetic beads functionalized with electrostatically neutral peptide nucleic acids (PNA) for the detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). A screen-printed carbon electrode was modified with a plasticized polymeric membrane. A SARS-CoV-2 specific peptide nucleic acid probe was designed and synthesized. We exploited the advantage of neutral PNAs to remove the negatively charged DNA probes that cause fouling due to the attraction of positively charged biomolecules. After specific binding of peptide nucleic acid to its complementary DNA target, the peptides were incubated with cationic magnetic nanoparticles. The potentiometric responses were recorded after applying a magnetic field for the rapid and sensitive detection of SARS-CoV-2. Various parameters including polymeric membrane composition, probe concentration and incubation time, amount and incubation duration of magnetic nanoparticles, the order of probe-target magnetic bead incubation, and the force of magnetic field effect were investigated. Under optimized conditions, SARS-CoV-2 DNA was detected in the linear range of 1.0 & times; 10-15-1.0 & times; 10-11 M with an LOD of 4.9 & times; 10-16 M. Moreover, the sensing performance of the developed biosensor in human saliva was evaluated, and the recovery rates were found to be 96-98%. For proof of concept, a smartphone-based near-field communication electrochemical analyzer was integrated into the developed biosensor for potentiometric measurements. This biosensor is promising, as the antifouling PNA probes provide a new concept for the development of sensitive biosensors for screening for COVID-19 in biological samples.
Keywords: ION-SELECTIVE ELECTRODES; COVID-19; TRENDS; Chemistry